INVENTORY CONTROL OF BROWN PAPER RAW MATERIALS USING THE MATERIAL REQUIREMENT PLANNING METHOD IN PAPER COMPANY - Sinta Khoiriyah Wulandari; Dwi Sukma Donoriyanto (Center for Study and Journal Management FTI UMI, 2022)
Inventory of raw materials is an essential element in the production process. The research was conducted in a paper company with different product demand problems each period, resulting in excessive raw material inventory in the warehouse and high inventory costs. Material Requirement Planning (MRP) is the right system to deal with uncertainty when planning raw material requirements. The lotting techniques used in this study are Lot For Lot (LFL), Economic Order Quantity (EOQ), and Fixed Period Requirements (FPR). For January 2021 - March 2022, the LFL lot size MRP method resulted in the smallest total inventory cost of Rp 92.228.707.169 and managed to save 9.2% of costs compared to the company's actual costs. Inventory control with LFL lot size for April 2022 – June 2023 requires 14 orders with the DSOCC raw material inventory 11.865.136,77 kg; OCC 5.256.037,55 kg; NDLKCA 4.262.881,19 kg; local box 3.340.998,93 kg and the total cost of inventory is Rp 110.075.072.816,14